Efferocytosis in dendritic cells: an overlooked immunoregulatory process - Ma, Yanyan; Jiang, Tangxing; Zhu, Xun; Xu, Yizhou; Wan, Ke; Zhang, Tingxuan; Xie, Miaorong (Frontiers in Immunology, 2024)
Efferocytosis, the process of engulfing and removing apoptotic cells, plays an essential role in preserving tissue health and averting undue inflammation. While macrophages are primarily known for this task, dendritic cells (DCs) also play a significant role. This review delves into the unique contributions of various DC subsets to efferocytosis, highlighting the distinctions in how DCs and macrophages recognize and handle apoptotic cells. It further explores how efferocytosis influences DC maturation, thereby affecting immune tolerance. This underscores the pivotal role of DCs in orchestrating immune responses and sustaining immune equilibrium, providing new insights into their function in immune regulation.